Nucleotide substitutions in CD101, the human homolog of a diabetes susceptibility gene in non‐obese diabetic mouse, in patients with type 1 diabetes. Issue 3 (25th November 2016) - Okuno, Misako; Kasahara, Yoshihito; Onodera, Masafumi; Takubo, Noriyuki; Okajima, Michiko; Suga, Shigeru; Watanabe, Nobuyuki; Suzuki, Junichi; Ayabe, Tadayuki; Urakami, Tatsuhiko; Kawamura, Tomoyuki; Kikuchi, Nobuyuki; et al.
Abstract: Aims/Introduction: Although genome‐wide association studies have identified more than 50 susceptibility genes for type 1 diabetes, low‐frequency risk variants could remain unrecognized. The present study aimed to identify novel type 1 diabetes susceptibility genes by newly established methods. Materials and Methods: We carried out whole‐exome sequencing and genome‐wide copy‐number analysis for a Japanese family consisting of two patients with type 1 diabetes and three unaffected relatives. Further mutation screening was carried out for 127 sporadic cases. The functional consequences of identified substitutions were evaluated by in silico analyses and fluorescence‐activated cell sorting of blood samples. Results: Whole‐exome sequencing and genome‐wide copy‐number analysis of familial cases showed co‐segregation of the p.V863L substitution in CD101, the human homolog of an autoimmune diabetes gene in the non‐obese diabetic mouse, with type 1 diabetes. Mutation screening of CD101 in 127 sporadic cases detected the p.V678L and p.T944R substitutions in two patients. The p.V863L, p.V678L and p.T944R substitutions were absent or extremely rare in the general population, and were assessed as 'probably/possibly damaging' by in silico analyses. CD101 expression on monocytes, granulocytes and myeloid dendritic cells of mutation‐positive patients was weaker than that of control individuals. Conclusions: These results raise the possibility that CD101 is a susceptibility gene for type 1 diabetes. Abstract : We identified nucleotide substitutions of CD101, an autoimmune diabetes gene in the NOD mouse, in familial and sporadic cases of type 1 diabetes. Fluorescence‐activated cell sorting analysis demonstrated that CD101 expression on monocytes, granulocytes, and myeloid dendritic cells of mutation‐positive patients was weaker than that of control individuals. These results raise the possibility that CD101 is a novel susceptibility gene for type 1 diabetes.